Developing English Foreign Language (EFL) Learners’ Speaking Skills through the Effectiveness of Community Language Learning (CLL) - Wulandari, Afrianti; Salsabilla, Salsabilla (CV. Tripe Konsultan, 2026)
This study aims to develop English Foreign Language (EFL) learners’ speaking skills through the effective implementation of Community Language Learning (CLL). Using a qualitative research approach, the study explored students’ experiences and perceptions of CLL in an EFL speaking classroom. Data were collected through interviews, classroom observations, and students’ reflective journals during several instructional sessions applying the CLL method. The collected data were analyzed thematically to identify key patterns related to students’ linguistic and affective development. The findings indicate that the use of Community Language Learning effectively enhanced students’ speaking skills and learning experiences. Six major themes emerged from the discussion: increased speaking confidence, reduced anxiety, peer support and collaboration, improvement in speaking fluency, learner autonomy, and the teacher’s role as a counselor. Students reported feeling more comfortable and motivated to speak English in a supportive and non-threatening classroom environment. The collaborative nature of CLL encouraged active participation and mutual assistance, while the teacher’s facilitative role helped students feel emotionally secure. As a result, learners demonstrated greater fluency, confidence, and responsibility for their own learning. In conclusion, the study suggests that Community Language Learning is an effective approach for developing EFL learners’ speaking skills, particularly in contexts where affective barriers such as anxiety and lack of confidence hinder oral communication. By addressing both emotional and linguistic aspects of learning, CLL offers a valuable alternative for enhancing speaking instruction in EFL classrooms.abstract is a concise and comprehensive summary of scientific articles.